Subclinical deformities of the hip are significant predictors of radiographic osteoarthritis and joint replacement in women. A 20 year longitudinal cohort study - Thomas, G; Palmer, A; Batra, R; Kiran, A; Hart, D; Spector, T; Javaid, M; Judge, A; Murray, D; Carr, A; Arden, N; Glyn-Jones, S (Elsevier, 2014)
Objective: Femoroacetabular Impingement (FAI) and Acetabular Dysplasia are common deformities, which have been implicated as a major cause of hip osteoarthritis (OA). We examined whether these subtle deformities of the hip are associated with the development of radiographic OA and total hip replacement (THR) in women. Design: A population-based, longitudinal cohort of 1003 women underwent pelvis radiographs at years 2 and 20. Alpha Angle, Triangular Index Height, Lateral Centre Edge (LCE) angle and Extrusion Index were measured. An alpha angle of greater than 65° was defined as Cam-type FAI. Radiographic OA and the presence of a THR were then determined at 20 years. Results: Cam-type FAI was significantly associated with the development of radiographic OA. Each degree increase in alpha angle above 65° was associated with an increase in risk of 5% (Odds Ratio (OR) 1.05 [95% confidence interval (CI) 1.01–1.09]) for radiographic OA and 4% (OR 1.04 [95% CI 1.00–1.08]) for THR. For Acetabular Dysplasia, each degree reduction in LCE angle below 28° was associated with an increase in risk of 13.0% (OR 0.87 [95% CI 0.78–0.96]) for radiographic OA and 18% (OR 0.82 [95% CI 0.75–0.89]) for THR. Conclusions: This study demonstrates that Cam-type FAI and mild Acetabular Dysplasia are predictive of subsequent OA and THR in a large female population cohort. These are independent of age, BMI and joint space and significantly improve current predictive models of hip OA development.